ANALYSIS OF THE OUTPUT VOLTAGE SPEKTRUM OF A PARAMETRIC MICROWAVE CONVERTER : ANALYSIS OF THE OUTPUT VOLTAGE SPEKTRUM OF A PARAMETRIC MICROWAVE CONVERTER - Vasilev, Dragomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
In this scientific paper, we have considered a method for determining the complex reflection coefficient based on spectral analysis of the output voltage of a parametric microwave converter.